Body height as a measure of the standard of living: Europe, America And Asia - Kopczyński, Michał (Roczniki Dziejów Społecznych i Gospodarczych, 2016)
Body height reflects the standard of living in the first 18–20 years of life, while its changes serve as an index measuring the wellbeing of the society. Steady growth of body height in the Polish territory started in the 1860s. The changes recorded in earlier periods were reversible: the highest average was noted in Late Middle Ages, with body height then regressing until mid-19th century. The evolution of body height in Japan and Korea is a reflection of genetic and environmental conditions. The Japanese were higher than Koreans in the mid-20th century, but as the level of economic development of both countries became equal, the height of Koreans surpassed the average height of the Japanese. Even more dramatic influence of the environment can be noticed in the comparison of the body height of South and North Koreans over the 20th century.